Development of A 2D Numerical Model for Pollutant Transport using FTCS Scheme and Numerical Filter - Maitsa, Tias Ravena; Hafiyyan, Qalbi; Adityawan, Mohammad Bagus; Magdalena, Ikha; Kuntoro, Arno Adi; Kardhana, Hadi (Makara Journal of Technology, 2021)
This study used the finite difference method to develop a numerical model for pollutant transport phenomenon simulation. Mathematically, the phenomenon is often described by the advection–diffusion differential equation, which is obtained from a combination of the continuity equation and Fick’s first law. The Forward Time Central Space (FTCS) scheme is one of the explicit finite difference methods and is used in this study to solve the model due to its simplicity in solving a differential equation. Yet, this method is currently unstable, which results in oscillations in the model. Thus, a numerical filter (Hansen) is added to the FTCS method to improve the stability of the model. The developed numerical model is applied to several 1D and 2D pollutant transport test cases. Simulation results are compared with those of existing analytical solutions to verify the developed model, and they show that the developed model can simulate the pollutant transport phenomenon well. Moreover, the numerical filter can increase the model stability.